SINTESIS SENYAWA DIMETILTIMAH(IV) N-BENZILMETILDITIOKARBAMAT DAN UJI ANTIBAKTERI TERHADAP Salmonella typhi DAN Staphylococcus epidermidis - Sanuddin, Mukhlis; Andriani, Medi; Yasril, Farih Rahma (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Antibacterial can inhibit growth or kill microorganisms. The purpose of this study is to synthesize and determine the antibacterial activity of the dimethyltin(IV) N-benzylmethylditiocarbamate. The research method used in this study is an experimental method. The compounds characterized using FTIR, 1H-NMR, 13C-NMR, compounds analyzed using FTIR obtained groups (C-H) 2912.51 cm-1, (C-N) 1192.01 cm-1, (C=S) 773.46 cm-1, (Sn-S) 360.69 cm-1, (Sn-C) 561.29 cm-1, (C-C) 1078.21 cm-1, the results of analysis from the 1H-NMR test were obtained 0.6552-0.8861 ppm (CH3), 2.5843-2.6479 ppm (CH2), and 7.0888-7.4345 ppm (Aromatic). The results of the analysis from the 13C-NMR test were obtained 4.1023-7.6992 ppm (CH3), 46.6439 ppm (CH2), 59.9685 ppm (C-N), 127-6009-135.1784 ppm (Caromatic), and 201.4111 (C-S2). Then the antibacterial activity test was carried out by the disc paper method with concentrations of 50 ppm, 60 ppm, and 70 ppm with the results of testing antibacterial activity with a concentration of 70 ppm resulting in the largest inhibitory zone with a strong category in Salmonella typhi 17.81 mm and Staphylococcus epidermidis 21.96 mm with a very strong category. Conclusion The compound dimethyltin(IV) N-benzylmethyldithiokarbate was successfully synthesized and formed a complex compound structure and has activity as an antibacterial agent with a very strong category.